2015
DOI: 10.1038/am.2015.83
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable thermo-responsive hybrid hydrogel: therapeutic applications in preventing the post-operative recurrence of breast cancer

Abstract: Smart hydrogels that undergo structural changes in response to stimuli (for example, pH, heat, light) have promising biomedical applications as delivery systems, especially for the locally controlled release of drugs. Early prevention of locoregional recurrence (LRR) is critical for patients who have undergone breast-conserving therapy. This work reports the preparation of a hybrid hydrogel system in which gold nanorods (GNRs) were doped into a thermally responsive hydrogel. A near-infrared (NIR) laser was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 41 publications
0
65
0
Order By: Relevance
“…This mechanism increases the efficiency of drug release at the cancer site in addition to hyperthermia of the cancerous cells. Ying Qu et al 293 developed a combined hydrogel system by doping gold nanorods (GNRs), as the photothermal agents, into the DOX embedded hydrogels. They demonstrated that efficient release of DOX from hydrogel matrix, by means of stimulating GNRs photothermal agents, resulted in a remarkable decrease of the tumor recurrence in mice 4T1 breast cancer models.…”
Section: Light-induced Thermoresponsive Nanocarriersmentioning
confidence: 99%
“…This mechanism increases the efficiency of drug release at the cancer site in addition to hyperthermia of the cancerous cells. Ying Qu et al 293 developed a combined hydrogel system by doping gold nanorods (GNRs), as the photothermal agents, into the DOX embedded hydrogels. They demonstrated that efficient release of DOX from hydrogel matrix, by means of stimulating GNRs photothermal agents, resulted in a remarkable decrease of the tumor recurrence in mice 4T1 breast cancer models.…”
Section: Light-induced Thermoresponsive Nanocarriersmentioning
confidence: 99%
“…29 For example, gold nanorods doped into a thermally responsive hydrogel made with methoxylpoly(ethylene glycol)-poly(ε-caprolactone)-acryloyl chloride, glycidylmethacrylated chitooligosaccharide, N -isopropylacrylamide, and acrylamide, were able to induce the contraction of the thermo-responsive hydrogels and trigger the release of loaded doxorubicin to inhibit breast cancer under NIR irradiation (Figure 3). 73 Other NIR-absorbing nanoparticles such as carbon nanotubes 113 and graphene oxide nanoparticles 116 were also incorporated into thermo-responsive polymers to harness NIR for remotely controlled drug delivery. Recently, upconversion core-shell nanoparticles made from NaYF 4 :TmYb (core = NaYF 4 :0.5 mol % Tm 3+ :30 mol % Yb 3+ ; shell = NaYF 4 , in a uniform hexagonal prism shape with an average length of 36.0 ± 1.1 nm and width of 32.0 ± 1.5 nm) capable of converting NIR light into UV light were also integrated with a photo-responsive hydrogel consisting of acrylamide monomer and the photocleavable PEG cross-linker.…”
Section: Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Over the past decades, different polymeric therapeutics have begun to make a vital contribution for tumor targeting in cancer therapy. In cancer drug delivery, different polymer based hydrogels have been designed and demonstrated as drug carrier systems [4] [5] [6,7] [8]. Among the several polymeric systems developed, systems containing biodegradable polymers have been used for localized drug delivery to control therapeutic drug level over a period of months, since the degradation of polymer is slow [9].…”
Section: Introductionmentioning
confidence: 99%